A study on solutions for wireless energy transfer limitations - Fincan, B.; Ustun, O. (Institution of Engineering and Technology, 2014)
One of the challenging problems of Wireless Energy Transfer (WET) is to provide higher efficiency values in spite of decreasing in mutual inductance between coils. For this reason, the study presents some limits such as the critical height and critical winding pitch of coils. This paper also proposes calculation methods for resistance, inductance and quality factor of coils with small error. These limits lead to decrease in proximity effect on resistance of coil in high frequency. Moreover, Energy Transfer Modulation Method (ETMM) is proposed since the quality factor of coil, which is curbed by the maximum ac rated voltage of resonance capacitor, is increased by ETMM and the system efficiency is enhanced simultaneously with the quality factor. However, ETMM does not always work on account of the high receiver loss factor. For this reason, the ETMM's boundaries are given in order to find out if ETMM raises the system efficiency or not. Finally, the best coil shape is investigated experimentally.